Scientific argumentations research for last 10 years: analysis bibliometric - Suliyanah, Suliyanah; Amiruddin, Mohd Zaidi; Prahani, Binar Kurnia (International Journal of Evaluation and Research in Education (IJERE), 2024)
The topic of scientific arguments is crucial to discuss because it is one of the basic sciences that has close links with other topics. Moreover, this science has a close relationship with the skills of the 21st century today. This study aims to reveal the current trends in the scientific argumentation field for the last 10 years based on the Scopus database. This study uses quantitative research through bibliometric studies with the keyword scientific argumentation year. The results of this study indicate that the number of article publications during the years 2012 to 2021 on the topic of scientific argumentation has increased on average. However, the most visible increase was in 2018-2021. The United States, Indonesia, and Germany dominated the publication of scientific argumentation topics from 2012 to 2021. As for the top authors were from the United States and Germany. Furthermore, in scientific argumentation, dominated by subject areas based on science, keywords used are argumentation, students, and scientific argumentation. There were several suggestions for the research, namely: i) the need for further research, especially on the differences and similarities of each argumentation; ii) the need to discuss the appropriate scope of argumentation at the appropriate learning level; iii) collaboration between universities that have a focus on this argumentation field. It is highly recommended that the research be more robust; and iv) future research must adapt to the current development of arguments so that the topic does not decline but continues to become the basis for studying other sciences.